Integration of Critical Thinking in “English for Change” Textbook for Grade XI: Content Analysis - Anastasia Layu; Ariyanti Ariyanti; Abdul Rohman; Arbain Arbain (Wadah Inovasi Indonesia, 2025)
This study aims to analyze the integration of Facione's Critical Thinking Framework in the textbook